Analisis Biaya Differensial Sebagai Dasar Pengambilan Keputusan Menerima atau Menolak Pesanan Khusus (Studi Kasus Pada PT Sathrusi Komoditi Indonesia - Elma , Eneng; Cahya Kusuma , Indra; Budi Setiawan , Ade; Anwar, Saepul (Jurnal Ilmiah Raflesia Akuntansi, 2024)
This research aims to find out how much idle capacity is available for special orders at PT Sathrusi Komoditi Indonesia, whether the decisions made by the company in accepting or rejecting special orders are correct. This type of research is quantitative descriptive research. The data collection methods used in this research were interviews, observation and documentation. The method used to analyze the data is the least squares method (Least Square Method). The results of the differential cost analysis carried out at PT Sathrusi Komoditi Indonesia were that the decision to accept a special order was correct because it earned an additional profit of IDR 297,200,716 from the decision to accept a special order for 44,400 kg of chili powder, even though the special order price was below the normal price set by the company.